2015
DOI: 10.4238/2015.december.7.7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of andrographolide in RAW 264.7 murine macrophage osteoclastogenesis by downregulating the nuclear factor-kappaB signaling pathway

Abstract: ABSTRACT. This study aims to investigate the effects of andrographolide (AGP) on osteoclast formation in RAW 264.7 murine macrophage cells. The effects of AGP on cell viability were determined in RAW 264.7 cells using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The effects of AGP on osteoclast formation were tested by osteoclast staining with tartrate-resistant acid phosphatase (TRAP). The effects of AGP on receptor activator of nuclear factor-kappaB (NFkappaB) ligand (RANKL)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…showed that andrographolide inhibited osteolysis by blocking NF-κB pathway. 79 These results confirm the vital role of andrographolide in regulating macrophage function. The phenotypic transition of M1 and M2 macrophages is important for the immune process, but the effects of andrographolide still need further investigation.…”
Section: Andrographolide Regulates the Function Of Macrophagessupporting
confidence: 62%
See 1 more Smart Citation
“…showed that andrographolide inhibited osteolysis by blocking NF-κB pathway. 79 These results confirm the vital role of andrographolide in regulating macrophage function. The phenotypic transition of M1 and M2 macrophages is important for the immune process, but the effects of andrographolide still need further investigation.…”
Section: Andrographolide Regulates the Function Of Macrophagessupporting
confidence: 62%
“…Wong et al found that andrographolide restored dexamethasone's inhibitory impact on LPS/IFN‐induced IL‐27 production 78 . Ren et al showed that andrographolide inhibited osteolysis by blocking NF‐κB pathway 79 . These results confirm the vital role of andrographolide in regulating macrophage function.…”
Section: Regulation Of Andrographolide On Immune Cellsmentioning
confidence: 78%
“…Additionally, andrographolide prevents inflammatory bone loss induced by LPS (Zhai et al, 2014). Importantly, it has been reported that andrographolide inhibits osteoclastogenesis in RAW 264.7 cells through downregulation of the NF‐κB signalling pathway (Ren & Zhou, 2015). On the other hand, andrographolide has the beneficial effect of osteoblast differentiation (Jiang et al, 2015; Yongyun et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This action was shown to contribute to the relief of CPT-11-induced intestinal mucositis. As a widely reported anti-inflammatory natural product, andrographolide has been shown to attenuate inflammation by inhibiting activation and function of macrophages 31 , 32 , 33 , 34 . For example, by inhibiting the NLR family pyrin domain containing 3 (NLRP3) inflammasome in macrophages, andrographolide alleviates colitis and prevents colitis-associated cancer 14 .…”
Section: Conclusion and Discussionmentioning
confidence: 99%